To Whom Does a Living Heritage Belong? Negotiations Over the Preservation of the Ottoman Legacy in Istanbul - Abdul Salam, Fawaz (Journal of the Council for Research on Religion, 2024)
The preservation of Ottoman heritage has been a contested topic in Turkey over the last few decades. While many studies have attended to the political and economic interests related to the restoration of Ottoman-era architectural complexes and buildings, this article draws attention to the intersecting aspirations and negotiations over the question of preservation by various actors in the historical Fatih district of Istanbul. The district’s historical importance is traced back to 1463, when the Ottoman ruler Mehmet II (ca. 1432–1481) decided to build a monumental mosque complex after the city’s conquest. The construction of additional monumental mosque complexes, madrasas (colleges), Sufi lodges, and shrines in the later Ottoman period transformed the district into a space reflecting the enduring political and socio-religious presence of Islamic and Ottoman urban traditions. Starting from the latter half of the nineteenth century, Ottoman modernization and early twentieth century Republican secularization significantly transformed the district’s built environment and everyday life. Over the last few decades, multiple agents have been involved in reviving the district’s Ottoman heritage, namely, Sufi orders, Muslim civil society organizations, and current government projects to restore Ottoman-era buildings. Drawing upon historical and ethnographic data collected in the district, the article argues that the meaning and function of Ottoman heritage are not static entities; rather, they are discursively constituted within shifting socio-political and economic contexts. While acknowledging the increasing commodification of tangible heritage in post-colonial Muslim cities, the article sheds light on how both shared and contested forms of belonging to the institutional and intellectual heritage of Islamic tradition, mediated by Ottoman-era architectural complexes and spaces, broaden our understanding of living heritage.